The Power of Myths on Environmental Preservation in Bali - Utami, Gek Wulan Novi (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
This research aims to find out the myths’ powerrelating to environmental preservation in Bali. Myth is humancreation that is rich of social and culture value within it todescribe phenomena around them. Myth is still exist even it turnsinto behavioural reference in Bali, moreover, Balinese rites arevery strong bounding people although modernization developsrapidly. It is assumed that myths ecology-related correlate tosemiological system that covers signifier, signified, and signwhich are potential influencing human perception andbehaviour to preserve environment. This research usesdescriptive-qualitative approach. The data is collected by depthinterview method and probing technique. Ecolinguistics’framework especially social praxis related that consists of threedimensions, namely a bio-logical, a socio-logical, and an ideological dimension, and also culture approach contributing inanalyzing data. It concludes that myths’ existence is very strong;it is powerful relating its impact to human, but powerless towardenvironment preservation